Estimation of genetic distances among various genotypes of blackgram (Vigna mungo (L.) Hepper) using D2 statistics - Md. Ayesha1, D. Ratna Babu1*, A. Prasanna Rajesh2, Lal Ahmed Md1 and V. Manoj Kumar3 (Electronic Journal of Plant Breeding, 2021)
The genetic distance assessment of forty blackgram genotypes was conducted employing Mahalanobis’ D2 statistics considering ten quantitative characters. All the studied genotypes were grouped in ten discrete clusters, among which cluster I was indeed the largest with thirteen genotypes followed by cluster V with eight genotypes, cluster IV with seven genotypes and cluster II with five genotypes. Cluster IX was digenotypic, other clusters III, VI, VII, VIII and X were all solitary. Cluster IV and IX had the greatest inter-cluster gap followed by cluster VIII and IX, clusters VII and IX, clusters II and IX, clusters III and IX, clusters V and IV, clusters IX and Cluster X and between cluster VI and IX, implying that a successful breeding programme can be begun by selecting diverse lines to improve productivity and other yield-related traits. In the current investigation, cluster X, cluster VI, cluster IV and cluster VIII were considered divergent enough and found to be the best. Hence, genotypes from these clusters viz., TU 94-2 from cluster IX, PU 31 from cluster VI, IPU 94-1 from cluster IV and LBG 623 from cluster VIII can be used in the crossing programme for additional genetic enhancement. Cluster IX had the highest mean score for traits viz., the number of clusters per plant, the number of pods per plant, pod length, test weight and grain yield per plant. The number of pods per plant provided the most to genetic diversity succeeded by the number of clusters per plant, days to maturity, plant height, pod length and test weight. As a result, in a crossing programme, selecting and utilising genotypes based on these traits will be more rewarding. Furthermore, taking into account the genotype disposition in various clusters, one can perform different possible crosses to produce heterotic hybrids or transgressive segregants, based on the nature of gene action regulating the traits.